Human-in-the-Loop Techniques: The Game-Changer in Facial Recognition - Sure, Tharun Anand Reddy (International Journal of Computer Sciences and Engineering, 2023)
Facial recognition technology has become increasingly ubiquitous, being used for everything from unlocking smartphones to identifying individuals. This technology has made our lives easier and more efficient in many ways, but it still has limitations. One of the most significant challenges facial recognition systems face is their accuracy, particularly for underrepresented demographic groups. This issue is further complicated by biases in the datasets used to train these systems. Facial recognition that produces inaccurate results can lead to severe consequences, including wrongful arrests and false accusations. Such technology must be thoroughly tested and regulated to avoid harming innocent individuals. Researchers have explored various methods for improving facial recognition algorithms to address these challenges. One promising approach is to leverage human expertise to supplement the machine-learning process. This article reviews some of the most effective human-in-the-loop approaches to enhance facial recognition systems` fairness, interpretability, and performance. These methods involve incorporating human feedback at different stages of the machine-learning pipeline, such as active learning, clean labeling, and human-AI collaboration in model development and evaluation. The results of these studies have shown that incorporating human judgment and domain knowledge can significantly improve facial recognition systems` accuracy and fairness. For example, active learning methods can help mitigate dataset biases by prioritizing the most informative samples for human labeling. Clean labeling can help ensure the training data is accurate and unbiased, while human-AI collaboration can improve model interpretability and generalization. The significance of these findings is that thoughtfully integrating human expertise into the facial recognition process can lead to more ethical and robust systems. By involving human feedback, we can mitigate the biases and limitations of machine learning algorithms and ensure that these technologies work for everyone, regardless of race, gender, or other demographic factors. Ultimately, this will help us build a more just and equitable society.